Preconcentration and Determination of Psychotropic Drugs in Urine Samples by Ion Mobility Spectrometry with Electrospray Ionization Coupling On-Line Single-Drop Liquid-Liquid-Liquid Microextraction - Shu Li (Journal of Analytical Methods in Chemistry)
A method for analysis of psychotropic drugs in urine is investigated using a novel single-drop liquid-liquid-liquid microextraction (SDLLLME) apparatus as an electrospray emitter in ion mobility spectrometry (IMS). In this method, ketamine and pethidine are back-extracted into the acceptor phase (water and methanol) from the water and methanol immiscible organic phase. Sensitivity of extraction is improved as it does not require further methanol-adding procedure. Factors affecting the extraction of psychotropic drugs are characterized, including organic solvent type, extraction time, and concentration of NaOH/Ac in the donor/acceptor phase. The best extraction sensitivity is obtained with 600 μL dodecane as the organic phase, 30 minutes extraction time, and 10 mL donor phase with 0.01 M sodium hydroxide (NaOH) and 3 μL acceptor phase with 0.5 M acetic acid (Ac). Using this method, the two analytes can be extracted and analyzed simultaneously, showing this method is valuable for field application.